SINERGISITAS PENGAWAS DAN KEPALA SEKOLAH DALAM SUPERVISI AKADEMIK GURU PAI SD DI KECAMATAN AIR PERIUKAN KABUPATEN SELUMA - Tutis Amimi (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2016)
This study aims to improve the implementation of the academic supervision done by supervisors of IslamicEducation and school principals Seluma. This research is a descriptive analytical research, gathering information on thestatus and symptoms existing at the time according to what their research is conducted. That is the subject of this researchis the superintendent, principals and teachers PAI. This research instrument with observation, interview, documentationstudy. To answer the problem formulation using descriptive research which is a non-hypothetical, so that the research stepsdo not need to formulate hypotheses. The results of this study indicate that the implementation of the program of theacademic supervision supervisor and school principals to PAI teachers in the district Air Periukan, has been implementedin accordance with the work program drawn up collectively between supervisors PAI and school principals in the groupIII Air Periukan districts. The collectivity built through the Council Working Group Principal (MKKKS) and TeachersWorking Group (KKG) PAI Air Periukan districts Seluma. Synergy supervisors PAI and school principals in the district AirPeriukan in doing academic supervision to teachers PAI already well established. PAI superintendent and chief academicsupervision SD develop programs through MKKKS.While the implementation of the academic supervision to teachersthrough KKG PAI PAI districts Seluma Air Periukan district.